2017
DOI: 10.4103/ijcm.ijcm_121_16
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perception regarding autism among primary school teachers: A cross-sectional survey from Pakistan, South Asia

Abstract: Background:Early detection and intervention seem to improve development in autistic children, and teachers form an important part of their early social environment.Objectives:The objective of this study was to assess baseline knowledge and misconceptions regarding autism among school teachers and evaluate factors influencing their knowledge.Materials and Methods:This is a cross-sectional survey enrolling primary school teachers using a self-administered questionnaire.Results:Seventy-three teachers (mean age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 10 publications
2
16
0
4
Order By: Relevance
“…A mean score of 5.59 was seen for the section regarding correct opinions for autism, with eight out of 13 being considered a good score, and a mean score of 6.84 for signs and symptoms was calculated, with a good score being decided as nine out of 14. The poor knowledge displayed by our participants is similarly seen in other studies, such as one conducted in Pakistan among pre-school teachers, of which only 50% were able to identify a majority of disease characteristics and one where only 17% of pre-school teachers being interviewed in China could answer more than 50% of the items accurately [ 13 - 14 ]. However, studies showing better awareness have also been conducted, such as a study among first-grade nursing and medical students in Istanbul where 70.9% were moderately aware of autism [ 15 ].…”
Section: Discussionsupporting
confidence: 75%
“…A mean score of 5.59 was seen for the section regarding correct opinions for autism, with eight out of 13 being considered a good score, and a mean score of 6.84 for signs and symptoms was calculated, with a good score being decided as nine out of 14. The poor knowledge displayed by our participants is similarly seen in other studies, such as one conducted in Pakistan among pre-school teachers, of which only 50% were able to identify a majority of disease characteristics and one where only 17% of pre-school teachers being interviewed in China could answer more than 50% of the items accurately [ 13 - 14 ]. However, studies showing better awareness have also been conducted, such as a study among first-grade nursing and medical students in Istanbul where 70.9% were moderately aware of autism [ 15 ].…”
Section: Discussionsupporting
confidence: 75%
“…Overall, in this review we found a lack of knowledge in most of the articles reviewed coinciding with prior reviews [61,62] and other studies [45]. We found that most of the articles revealed low [64,66,68,71,75,76,79,[84][85][86]95] or medium [65,67,73,74,77,78,80,82,91] levels of knowledge about ASD among their participants, coinciding with prior studies [21,25,36,37]. Indeed, most of the studies showed misconceptions [75,85,91] and gaps, or a lack of knowledge [71,77,85,95].…”
Section: Teachers' Knowledge Of Asd and Moderators That Possibly Influence Asdsupporting
confidence: 71%
“…In the case of studies with a pre-and post-test, we wrote down the first test result; in the other two situations, we calculated the average among article results. Eleven studies [64,66,68,71,75,76,79,[84][85][86]95] revealed low levels of knowledge regarding ASD among their participants; nine studies [65,67,73,74,77,78,80,82,91] reported medium knowledge, and five studies [65,87,89,90,92] described a high level of knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, teachers expressed neutral attitudes towards the inclusion of students with autism in general education classrooms (Engstrand & Roll-Pettersson, 2012;Srivastava et al, 2017a), whereas special education teachers, who taught students with autism, had low to moderate levels of knowledge regarding autism, as well as low to moderately effective teaching practices for their students (Hendricks, 2011). Finally, in-service, preservice, and future teachers had no (or limited) knowledge as well as basic misconceptions about autism and the needs of students with autism in inclusive education classes (Ayub et al, 2017;Barned et al, 2011;Finch et al, 2013;Johnson et al, 2012;Rakap et al, 2016;Yasar & Cronin, 2014;Young et al, 2017).…”
Section: Discussion -Conclusionmentioning
confidence: 99%
“…The survey results reveal that participants felt inadequate in both teaching and dealing with students with autism, while there were not asking for assistance and training to improve their skills. Ayub et al (2017) investigated the knowledge and perceptions of 73 teachers (mean age of 34 years, 66% females) in Pakistan, South Asia. Their results reveal that there are gaps in awareness and knowledge of the teachers.…”
Section: Turkeymentioning
confidence: 99%